An axial semi-rigid connection model for cross-type transverse branch plate-to-CHS joints. (15th February 2019) - Zhao, Bi D.; Chen, Yu; Liu, Cheng Q.; Wu, Han D.; Wang, Tao; Wei, Xiao D.
Highlights: Develops a model to predict the semi-rigid performance of branch plate-to-CHS joint. FE model for X-type branch plate-to-CHS joints is calibrated by test results. Simplified theoretical formula for axial initial rigidity of the joints is created. Parametric study on 7 parameters is carried out and their formulas are established. Comparison analysis results show the axial semi-rigid model has a good reliability. Abstract: This study is aimed to develop a model to accurately predict the semi-rigid performance of branch plate-to-circular hollow section (CHS) joints for tubular structures. First of all, a finite element (FE) model for cross-type transverse branch plate-to-CHS (CTTPCHS) joints is calibrated by test results. Based on the improved Menegotto-Pinto equation and the axial load-local deformation curves that are resulted from the calibrated FE model, an axial semi-rigid connection model for CTTPCHS joints is established, which has 7 parameters including the axial initial stiffness. Then, the method to obtain 7 parameters is determined, and a theoretical formula for axial initial stiffness of the joints is established based on the quarter-circular arch model. The complex expression of the formula is simplified to the product of an exponential function and a power function. In addition, a numerical parametric study on 7 parameters is carried out by the calibrated FE model. And based on the results of parametric analysis and multivariate nonlinear regression analysis, the parametric formulas for the 7 parameters are established. Finally, a comparison between the FE analysis results and the semi-rigid connection model calculation results from the parametric formulas is made, which shows the axial semi-rigid connection model a good reliability.